Unequal Efficacy of Different Infarct Location in Predicting Futile Recanalization of Patients With Acute Ischemic Stroke - Li, Zhao-shuo; Zhong, Hai-long; Zhou, Teng-fei; He, Ying-kun; Li, Qiang; Wang, Zi-liang; Zhu, Liang-fu; Wen, Chang-ming; Han, Jian-feng; Li, Tian-xiao (Frontiers in Neurology, 2022)
Abstract Objectives: Endovascular thrombectomy (EVT) is a standard treatment for acute ischemic stroke (AIS) caused by large vessel occlusion, while futile recanalization is the main factor influencing the prognosis. The present study aimed to investigate the efficacy of different infarct sites in predicting futile recanalization of AIS patients. Methods: Data were obtained from two multicenter, prospective, randomized, controlled trials , which were concurrently conducted in China. Cases achieving a successful recanalization and with complete data of preoperative Alberta Stroke Program Early Computed Tomography score (ASPECTS) and 90d follow-up were included. The ASPECTS sub-regions were used to mark different infarct location in the two cerebral hemispheres. First, the distribution of each ASPECTS sub-region in the left and right hemispheres and the whole brain was analyzed, respectively. Then, the regions that were be associated with futile recanalization were initially assessed by a univariate model. Afterwards, a multivariate logistic regression model was used to identify the efficacy of different infarct sites in predicting futile recanalization. Results: A total of 336 patients were included in this study with median age 65 years(IQR:51-74), of whom 210 (62.50%) patients were male, and 189 (56.25%) met the definition of futile recanalization. The correlation between each ASPECTS subregion and poor outcome was different when it was restricted to a specific cerebral hemisphere. Moreover, in the left hemisphere, internal capsule region (OR:1.42, 95%CI:1.13-1.95, P=0.03) and M3 region (OR:2.26, 95%CI:1.36-3.52, P=0.001), and in the right hemisphere, M6 region (OR:2.24, 95%CI:1.32-3.36, P=0.001) showed a significantly higher efficacy in predicting futile recanalization. Conclusion: The efficacy of different infarct location in predicting futile recanalization is different. Different preoperative patterns of the high efficiency regions in the infarction core or penumbra can guide the thrombectomy decision-making.